2003
DOI: 10.1097/01.rlu.0000053407.04034.b1
|View full text |Cite
|
Sign up to set email alerts
|

Power Doppler Sonography Versus Tc-99m DMSA Scintigraphy for Diagnosing Acute Pyelonephritis in Children

Abstract: PURPOSE This study assessed the role of renal power Doppler ultrasonography (PDU) to identify acute pyelonephritis (APN) and to determine whether PDU can replace Tc-99m DMSA renal scintigraphy in the diagnosis of APN in children. METHODS A prospective study was conducted in 40 infants and young children (78 kidneys were evaluated) with a mean age of 25.9 months (range, 1 to 68 months) who were hospitalized with a first episode of high fever and bacteruria, possibly APN. All children were examined by PDU and Tc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 24 publications
2
28
0
2
Order By: Relevance
“…This study had limitations, since uncooperative children were excluded. In our previous report of 40 children, the sensitivity of PDU was 74% and the specificity was 94%, but the main shortcoming of this study was the lack of repeated DMSA scan for accurate definition of APN [28]. A high specificity of PDU (95%) was reported also by El Hajjar et al [29].…”
Section: Discussionmentioning
confidence: 51%
“…This study had limitations, since uncooperative children were excluded. In our previous report of 40 children, the sensitivity of PDU was 74% and the specificity was 94%, but the main shortcoming of this study was the lack of repeated DMSA scan for accurate definition of APN [28]. A high specificity of PDU (95%) was reported also by El Hajjar et al [29].…”
Section: Discussionmentioning
confidence: 51%
“…Eggli et al (18) were the first investigators who showed that the sensitivity of USG in detecting inflammation in renal perenchyma increased from 38% to 63% with As a result, they found the sensitivity and specificity values to be 92.1% and 93.8% for DMSA, 86.8% and 87.5% for CT, 89.50% and 87.5% for magnetic resonance imaging (MRI) and 74.3% and 56,7% for PDUS. After this study, more satisfactory results were published both for adult and pediatric patient groups (4,5,7,10). In fact, a marked advancement occured in the USG technology after the first studies which evaluated the success of this method and the sensitivity has been reported to be 74-89% in recent studies (19,20).…”
Section: Discussionmentioning
confidence: 63%
“…Therefore, the diagnosis of acute pyelonephritis (APN) should be made timely, accurate treatment should be administered, risk factors should be determined and the patient should be referred accordingly. However, it is mostly difficult to definetely differentiate APN from lower UTI by clinical findings and acute phase reactants which have low sensitivity and specificity especially in children below the age of 2 years (2,4,6). Currently, Tc-99m dimercaptosuccinicacid (DMSA) is considered the gold standard imaging method in detecting renal parenchymal involvement in patients diagnosed with APN (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[16][17] Subsequent renal parenchymal changes occur in 40% of those with VUR and 6% of those without VUR. 18 Surgical management gains priority with regard to degree of parenchymal involvement.…”
Section: Discussionmentioning
confidence: 99%